Validation of in-vitro tests of zirconia-ceramic inlay-retained fixed partial dentures: a finite element analysis - Waldecker, Moritz; Rues, Stefan; Rammelsberg, Peter; Bömicke, Wolfgang (Dental materials, 2019)
Objective - In the past, discrepancies between laboratory results and clinical behavior have been observed for all-ceramic restorations. This analysis of fracture resistance of zirconia-based inlay-retained fixed partial dentures (IRFPDs) aimed at identifying correlations between an in-vitro test setup and the clinical situation. The effects of tooth material, tooth mobility, restoration design, load direction, and different cements were taken into account. - Methods - The in-vitro test model and IRFPD were reverse engineered (Geomagic DesignX) and meshed predominantly with hexahedral elements (approx. 230,000 elements). Homogenous, linear-elastic behavior was assumed for all materials. On the basis of the calculated stresses (ANSYS 18.2) and already known strength distributions for the restorative materials fracture resistance of the complete restoration and force at initial damage (fracture within the veneer) was estimated on the basis of the principal stress hypothesis. Differences depending on the assumed clinical situation and effects of different variables on fracture resistance were evaluated. - Results - All variables tested in the finite element analysis affected the calculated fracture resistance of the IRFPD. Use of resin teeth led to an underestimation of fracture resistance by up to −57%, whereas fracture resistance of IRFPDs on metal abutment teeth was close to the clinical reference (−6% to +15%). Good correlation between the clinical scenario and that using metal teeth could only be achieved when the natural resilience of the abutment teeth was simulated. - Significance - When testing fracture resistance of zirconia-based IRFPDs, metal abutment teeth in combination with simulated tooth resilience can reflect the clinical situation accurately.
Gesehen am 06.09.2019